A study on customers perception towards online banking during covid-19 - CHERUKUR, MR. RAM BABU; MR. SIVAKUMAR S (The journal of contemporary issues in business and government, 2020)
Online banking is increasingly becoming popular because of convenience and flexibility. The present paper explores the major factors responsible for internet banking based on respondents’ perception on various internet applications. It also provides a framework of the factors which are taken to assess the internet banking perception. The banking industry has been rapidly developing the use of online banking as an efficient and viable tool to create customer value. It is one of the popular services offered by the traditional banks to provide speedier and reliable services to online users. With the rapid development of computer technology as a commercial tool, Internet banking can be used to attract more customers to perform banking transactions in related banks. However, the main problem of Internet banking faced by the providers is that a large number of the banks’ customers are not willing to use the Internet banking services offered. This happened due to the services offered through Internet banking have yet to satisfy their customers. Customer satisfaction is an important factor to help banks to sustain competitive advantages. Therefore, the purpose of this research is to search and examine the factors which influence customer satisfaction towards Internet banking.